2020
DOI: 10.1002/hon.2757
|View full text |Cite
|
Sign up to set email alerts
|

Improving the international prognostic index score using peripheral blood counts: Results of a large multicenter study involving 520 patients with diffuse large B cell lymphoma

Abstract: The main purpose of this study was to assess whether it is possible to improve the prognostic impact of international prognostic index (IPI) score by combining it with peripheral blood counts. Thus, we evaluated the prognostic power of lymphocyte, neutrophil, and monocyte counts in 520 patients with diffuse large B cell lymphoma treated with R-CHOP, confirming that these parameters have a strong impact on overall survival (OS). Using revised IPI (R-IPI), 44% of patients were categorized as poor-risk and showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The study showed that PLR≥150 in DLBCL cases at diagnosis correlates positively with increased LDH>230UI/L(AUC=0.638, P=0.026,95%CI).In agreement to prior findings (Chang et al, 2015) and ECOG-PS score 2-4(AUC =0.609 P = 0.075, 95% CI) Figure 3B. In agreement with the previous finding by (Marcheselli et al, 2020).…”
Section: Plr≥150/ Clinicopathological Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…The study showed that PLR≥150 in DLBCL cases at diagnosis correlates positively with increased LDH>230UI/L(AUC=0.638, P=0.026,95%CI).In agreement to prior findings (Chang et al, 2015) and ECOG-PS score 2-4(AUC =0.609 P = 0.075, 95% CI) Figure 3B. In agreement with the previous finding by (Marcheselli et al, 2020).…”
Section: Plr≥150/ Clinicopathological Characteristicssupporting
confidence: 89%
“…Approximately 50 to 60 percent of patients are affected by advanced-stage diffuse disease III and IV (Chang et al, 2015). The international prognosis index is subjected to the current standard prognostic system for lymphoma but it has been suggested that the international prognosis index (IPI) might not be perfect in risk classification, diagnosis, and early diagnosis in DLBCL patients (Marcheselli et al, 2020). Further evaluation in prior reports stated RBC and HB are internal signals that initiate an inflammatory response, tumor growth, and resistance to chemotherapy (Moses & Brandau, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the prognostic capability of IPI upon treatment with R-CHOP–based immunochemotherapy, 25 , 26 , 27 we found a correlation of IPI with genetic subtypes and LME categories based on a large cohort of patients with newly diagnosed DLBCL, demonstrating different genetic and tumor microenvironmental signatures of the IPI in DLBCL.…”
Section: Discussionmentioning
confidence: 67%